Synergy-Based Small-Molecule Screen Using a Human Lung Epithelial Cell Line Yields ΔF508-CFTR Correctors That Augment VX-809 Maximal Efficacy - Phuan, Puay-Wah; Veit, Guido; Tan, Joseph; Roldan, Ariel; Finkbeiner, Walter E.; L. Lukacs, Gergely; Verkman, A.S. (Molecular pharmacology, 2014)
The most prevalent cystic fibrosis transmembrane conductance regulator (CFTR) mutation causing cystic fibrosis, ΔF508, impairs folding of nucleotide binding domain (NBD) 1 and stability of the interface between NBD1 and the membrane-spanning domains. The interfacial stability defect can be partially corrected by the investigational drug VX-809 (3-[6-[[[1-(2,2-difluoro-1,3-benzodioxol-5-yl)cyclopropyl]carbonyl]amino]-3-methyl-2-pyridinyl]-benzoic acid) or the R1070W mutation. Second-generation ΔF508-CFTR correctors are needed to improve on the modest efficacy of existing cystic fibrosis correctors. We postulated that a second corrector targeting a distinct folding/interfacial defect might act in synergy with VX-809 or the R1070W suppressor mutation. A biochemical screen for ΔF508-CFTR cell surface expression was developed in a human lung epithelium–derived cell line (CFBE41o−) by expressing chimeric CFTRs with a horseradish peroxidase (HRP) in the fourth exofacial loop in either the presence or absence of R1070W. Using a luminescence readout of HRP activity, screening of approximately 110,000 small molecules produced nine novel corrector scaffolds that increased cell surface ∆F508-CFTR expression by up to 200% in the presence versus absence of maximal VX-809. Further screening of 1006 analogs of compounds identified from the primary screen produced 15 correctors with an EC50 < 5 µM. Eight chemical scaffolds showed synergy with VX-809 in restoring chloride permeability in ∆F508-expressing A549 cells. An aminothiazole increased chloride conductance in human bronchial epithelial cells from a ΔF508 homozygous subject beyond that of maximal VX-809. Mechanistic studies suggested that NBD2 is required for the aminothiazole rescue. Our results provide proof of concept for synergy screening to identify second-generation correctors, which, when used in combination, may overcome the “therapeutic ceiling” of first-generation correctors.